Ocupation and movilization in Patagonia rural towns: An agrarian point of view - Bendini, Mónica; Steimbreger, Norma (Centro de Historia Argentina y Americana, 2011)
The study of occupations and mobilities in rural towns introduces us to the relationship between agriculture and rurality, and to "the" rural as non residual space in front of "the" modern and "the" urban. A related question has to do with the centering/des-centering of the agro, either by monoactivity or by the main occupation in case of multiple occupations, as well as the form taken by the relations between countryside (rural scattered) and town (rural aglomerated). On the other hand, it relates to the nature of the rural world as social space, differentiated and built, a place of life and work. From a glance that makes visible the role of the agro in the rural, we show diverse occupational nets and displacements from case studies which exemplify the issues raised: two rural towns with variability in agro development and the social organization of agriculture. On the one hand, it is a rural town with high population growth located in an area of agricultural expansion, with company scale organization, predominance of wage relations of production and agricultural occupations, mostly important presence of seasonal migrant workers. On the other hand, a rural town located in a region historically marginal and slow down, sparsely populated, in an area of plateau dedicated to extensive livestock breeding where there coexist large farms and peasant units; recent population growth, traditional agro occupations and pluriactivity also traditional. The empirical research show the diverse spatial movements, the occupations and their forms of combination, the principality of the agro activity and related ones, and the consequent identity character of those towns. The findings lead us to raise the issue of the breakdown of the single occupation and of the complexity of the link countryside - town. The nowadays concern of the agro in the rural, and of the rural "living" towns, are matters that new rurality and globalization issues have been sometimes overshadowed.